2016
DOI: 10.1001/jamadermatol.2015.4498
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Findings and Systemic Associations in Women With Polycystic Ovary Syndrome

Abstract: IMPORTANCE Understanding of the associations among cutaneous findings, systemic abnormalities, and fulfillment of the diagnostic criteria in women suspected of having polycystic ovary syndrome (PCOS) is incomplete. OBJECTIVE To identify cutaneous and systemic features of PCOS that help distinguish women who do and do not meet the diagnostic criteria. DESIGN, SETTING, AND PARTICIPANTS Retrospective cross-sectional study of a racially diverse referred sample of women seen at the University of California, San Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 49 publications
4
51
3
5
Order By: Relevance
“…5 Patients with PCOS are commonly first seen by a dermatologist. 6 Diagnosis is mainly clinical. Dermatologists often play a significant role in its management.…”
Section: Introductionmentioning
confidence: 99%
“…5 Patients with PCOS are commonly first seen by a dermatologist. 6 Diagnosis is mainly clinical. Dermatologists often play a significant role in its management.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, women followed the recommended macronutrient composition of weight-loss diets for obese PCOS women adopted by Moran et al [14], showed a significant weight reduction, acclaiming the benefits of that type of diet therapy. Weight reduction through diet control therapy, was adopted in the current study as obesity play a significant role in the pathology of PCOS [6], and though conservative treatment is recommended for PCOS through lifestyle modification [17], the term lifestyle modification is somehow vague. Lim et al [20], reported their disagreement with such hypothesis concerning the association between the lack of exercise and the clinical or biochemical characteristics typical of PCOS, supporting the concept of weight reduction in favor of exercise in the field of lifestyle modification.…”
Section: Discussionmentioning
confidence: 99%
“…Most women (91.7%) meeting the criteria for PCOS had at least one skin finding, with higher burden of acne, hirsutism, and acanthosis nigricans (AN) than women who did not meet the criteria [6]. In the present study, following the recommended diet for 12 weeks has significantly reduced acne and hirsutism scores and maintained that effect for another 12 weeks, which may be beneficial for improving all the other symptoms related to it, as beside all the previous mentioned symptoms, PCOS women may display several psychological disorders such as depression, anxiety, marital and social problems, which aggravate the psychological impact of hirsutism as, not only is hirsutism itself a major concern for women diagnosed with PCOS, but the time and effort spent eliminating it aggravates the distress [7], hence emerge the importance of measuring hirsutism because hirsutism score is the main predictor of psychological distress [34] and can significantly predict reduction of body hair, emotions, menstrual problems, weight and infertility problems, in their order of severity [7] Hirsutism was also associated with a higher mean HOMA-IR, body mass index, and triglycerides level, as well as a lower HDL-C level [6]. Although acne is not a reliable marker of hyperandrogenism, Androgens are important in the development of acne and its prevalence is high among patients who meet PCOS diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AN is usually associated with obesity, insulin resistance and PSOS. 8 Hyperkeratosis is increased in melanin pigmentation resulting in the dark color of AN. 9 There is a subtle infiltrate composed of lymphocytes, plasma cells, and neutrophils as well as horn pseudocyst formation.…”
mentioning
confidence: 99%